Personalised cancer medicine Future crafting in the genomic era - Kerr, Anne (Manchester University Press, 2021)
What does it mean to personalise cancer medicine? Personalised cancer medicine explores this question by foregrounding the experiences of patients, carers and practitioners in the UK. Drawing on an ethnographic study of cancer research and care, we trace patients', carers' and practitioners' efforts to access and interpret novel genomic tests, information and treatments as they craft personal and collective futures. Exploring a series of case studies of diagnostic tests, research and experimental therapies, the book charts the different kinds of care and work involved in efforts to personalise cancer medicine and the ways in which benefits and opportunities are unevenly realised and distributed. Investigating these experiences against a backdrop of policy and professional accounts of the 'big' future of personalised healthcare, the authors show how hopes invested and care realised via personalised cancer medicine are multifaceted, contingent and, at times, frustrated in the everyday complexities of living and working with cancer. Tracing the difficult and painstaking work involved in making sense of novel data, results and predictions, we show the different futures crafted across policy, practice and personal accounts. This is the only book to investigate in depth how personalised cancer medicine is reshaping the futures of cancer patients, carers and professionals in uneven and partial ways. Applying a feminist lens that focuses on work and care, inclusions and exclusions, we explore the new kinds of expertise, relationships and collectives involved making personalised cancer medicine work in practice and the inconsistent ways their work is recognised and valued in the process.